Geochemistry of Cenozoic Plutonic Rocks in the Extra-Andean Southern Patagonia as Evidence for a Magmatic Arc Migration Process - Sanchez-Valenzuela, A (SERVICIO NACIONAL GEOLOGIA MINERVA, 2021)
In this work, we present the results of a petrographic and geochemical study that involves seven Cenozoic plutons located in a NS trending belt in western Patagonia, south of the present Chile Triple-Junction and to the east of the present magmatic arc. Four plutons were studied in the northern end, and three in the southern part of the belt. The petrographic and geochemical characteristics (major and trace element contents, eNd t, Sr-87/Sr-86 initial ratios), of these plutons are different enough to propose a further classification for them: Only the Monte Balmaceda intrusive complex in the southern end of the belt is alkaline (sensu stricto). The Rio de Las Nieves and San Lorenzo plutons in the northern area, and the Torres del Paine intrusive complex, in the southern area have "intra-plate transitional" calcalkaline affinity. Paso de Las Llaves and Cerro Negro del Ghio plutons in the northern area, and Cerro Donoso pluton in the southern area show "arc transitional" calc-alkaline character. The "transitional" character, together with the pluton s location, and their regional geological context, can be explained by a Mio-Pliocene eastward arc migration coeval with the beginning of the Chile Rise subduction. A slab flattening hypothesis is favoured to explain the arc-migration, which together with the different length and time of arrival of the Chile Rise segments to the subduction zone, contributed to the heterogeneous geochemistry of the studied plutons.